Pendampingan identifikasi faktor permasalahan perkembangan peserta didik di SMA Negeri 2 Taliwang - Larassati, Minten Ayu (Nur Science Institute, 2022)
Mentoring aims to identify the factors that cause the development of students at SMA Negeri 2 Taliwang. In mentoring, data is collected using the interview method, with questions and answers given directly to the counseling teacher and students. This mentoring activity is carried out in two stages. The first stage is the identification of learning problems in students. The second is identifying problems among teachers—the results of the mentoring show that there are two factors. The first factor is the internal factor, namely the family, and the second is the external factor, namely the school environment. Another inhibiting factor is the influence of technological developments and social media. Social media dramatically affects students. It is not directed. It can threaten today's younger generation. Therefore, the role of parents and teachers is needed to be able to pay attention and direct it while still taking the positive value of technological progress.